BONE DENSITY OF THE LUMBAR SPINE L1-L4 AND FEMUR NECK ON CHILDBEARING AGE WOMAN WHO ARE IMPLANT AND NON HORMONAL CONTRACEPTIVES ACCEPTORS. - Kuswati Kuswati; Rohmi Handayani (Universitas Andalas, 2018)
mplant contraception is one type of contraceptive in the form of an implant made of silastik rubber containing the progestin hormone (levonogestrel) attached to the upper arm. This contraceptives are effective enough to prevent pregnancy in long-term with a lifetime of 3 years for 2 sticks and 1 stick implant. The main principle of levonorgestrel implants was to inhibite the ovulation resulting suppression of estrogen production. Estrogen is one of the important factors in bone remodeling. This becomes our concerns about the effect of implant use on the bone health status of the acceptors. The objective of this study is to determine mean difference of bone mineral density of the Lumbar Spine L1-L4 and Femur Neck on childbearing age woman who are implant acceptors and non hormonal family planning acceptors.This study was analytic survey with cross sectional design. The population in this study were all childbearing age woman in the work area of South Klaten Public Health Center. The sample were 30 people using purposive sampling. Data analysis was performed using Unpaired T-test with p ≤ 0,05. The result of examination on implant acceptor group totaling 15 people shown that the average of T-Score Lumbar Spine L1-L4 bone density was 0,51 and T-score of Femur neck bone was 0,1. While the results of bone density examination in the group of acceptor non hormonal totaling 15 people shown that the average value of T-score Lumbar Spine L1-L4 was 0.72, whereas the mean value of T-score of femur neck bone was 0.06. Unpaired T-Test statistic test for difference of bumble density of Lumbar Spine L1-L4 and Femur Neck between the two groups obtained P value 0.611 and 0.889 (P> 0,05). So there is no statistically significant difference between Lumbar spine L1-L4 and Femur neck bone density on childbearing age woman who are non-hormonal and implant acceptors. Keyword: Bone density, Lumbar Spine L1-L4, Femur neck, Implant, non hormonal Contraceptive